Comparison of the effectiveness of pirfenidone and nintedanib in patients with advanced stage idiopathic pulmonary fibrosis - Degirmenci, Guliz; Satici, Celal; Azakli Yazici, Damla; Cetinkaya, Nazim; Erdem, Umut; Demirkol, Baris; Erinc, Aysegul (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Idiopathic Pulmonary Fibrosis (IPF) is a progressive, fatal lung disease with high mortality, especially in advanced stages, defined as forced vital capacity (FVC) ≤50% and/or diffusing capacity of the lungs for carbon monoxide (DLCO) ≤30% of predicted values. While antifibrotic therapies, such as nintedanib and pirfenidone, are effective in mild to moderate IPF, their efficacy in advanced-stage IPF remains unclear due to the exclusion of these patients from major clinical trials.  This study aimed to compare the effectiveness of nintedanib and pirfenidone on mortality and to identify predictors of mortality in patients with advanced-stage IPF.Methods: This retrospective cohort study included 198 advanced-stage IPF patients treated with nintedanib (n=91) or pirfenidone (n=107) between 2017 and 2023. Demographic, clinical, and radiological data were collected. Mortality predictors were analyzed using multivariate Cox regression, and survival outcomes were compared using adjusted Kaplan-Meier curves.Results: Independent predictors of mortality were found to be six-minute walk distance (HR=0.99, 95% CI: 0.996–0.999, p=0.049), pulmonary fibrosis score ≥150 (HR=1.86, 95% CI: 1.07–3.22, p=0.026), and heart failure (HR=2.24, 95% CI: 1.18–4.26, p=0.014). After adjusting for these factors, no significant differences in mortality were observed between the nintedanib and pirfenidone groups.Conclusions: Nintedanib and pirfenidone showed comparable effectiveness in reducing mortality among advanced-stage IPF patients. Future clinical trials should include advanced-stage patients to better evaluate treatment efficacy in this population.